2021
DOI: 10.1590/2317-1782/20202020128
|View full text |Cite
|
Sign up to set email alerts
|

Kymographic characteristics of voice in women with Polycystic ovary syndrome

Abstract: Purpose: Polycystic ovary syndrome (PCOS) is heterogenous condition with commonly associated symptoms include irregular menstrual cycle, hirsutism, baldness, adult acne, and weight gain There have been few attempts at profiling the voice characteristics of women with polycystic ovary syndrome. Videokymography enables to detect even subtle variations in vocal fold vibrations. The aim of the present study was to study the videokymographic characteristics among women with PCOS. Methods: A cross-sectional study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 22 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…The age of patients ranged between 18 and 39 years. A total of 4 prospective, monocentric studies were included [3][4][5][6]. The main characteristics of the studies, including patient's inclusion and exclusion criteria, endpoint/outcomes evaluated, and tools used for the research, can be found in online supplementary materials Table S1.…”
Section: Study Characteristics and Patients' Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The age of patients ranged between 18 and 39 years. A total of 4 prospective, monocentric studies were included [3][4][5][6]. The main characteristics of the studies, including patient's inclusion and exclusion criteria, endpoint/outcomes evaluated, and tools used for the research, can be found in online supplementary materials Table S1.…”
Section: Study Characteristics and Patients' Characteristicsmentioning
confidence: 99%
“…Data on perceived voice quality were assessed by standardized and non-standardized scales and were reported in 4 studies [3][4][5][6]. Unfortunately, due to the different parameters and questionnaires tested in the studies considered for this review, the data were not comparable in order to perform a meta-analysis.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%
See 3 more Smart Citations